Management of neglected ACL avulsion fractures: a case series and systematic review. (August 2017) - Chouhan, D.K.; Dhillon, M.S.; John, R.; Khurana, A.
Abstract: Introduction: Neglected tibial eminence avulsion fractures of the anterior cruciate ligament (ACL) are uncommonly seen in modern times, but are fairly common due to a missed diagnosis/mismanagement in developing countries. Objectives: To determine the outcomes after open reduction and internal fixation of late presenting ACL avulsion fractures, and to review the literature for similar cases, in an attempt to evaluate the ideal surgical management in this unique scenario. Study design: Retrospective observational study and systematic review Materials: The study included 10 male and 2 female cases (mean age 29.9 years). Patients were assessed for the pre-operative knee range-of-motion (ROM), flexion deformity and stability; functional assessment was conducted using the Lysholm scale, both pre and post-operatively. Open reduction and internal fixation with two partially threaded screws (via a mini anterior approach) was performed in all 12 cases. All patients were clinically followed up for a minimum duration of 12 months. We searched PubMed, Embase and Cochrane databases from the period of inception to January 15, 2017 for similar case series/reports involving management of chronic/neglected ACL avulsion fractures and systematically reviewed these studies following standard PRISMA guidelines. Results: The median duration of presentation after injury was 12 months (range 3 to 312 months; mean 45.3 months). The mean follow-up duration was 24.1 months (range 12–48 months). All patients achieved normal knee extension except one patient who had a residual 5° flexion contracture. On physical examination, Lachman and pivot-shift tests were negative in all but 1 patient. No case required ACL reconstruction, and the fractures united radiologically within 12 weeks; all patients regained former activity levels. Discussion: Eleven published studies, mainly case reports, reported on the management of chronic/neglected ACL avulsion fractures. Arthroscopic suture/wire fixation, arthroscopic debridement of avulsed fragment and open reduction, internal fixation (ORIF) with screws are the described techniques for this uncommon entity. However, anatomic reduction of ACL avulsion fractures is difficult arthroscopically as crater depth assessment and repositioning of the avulsed fragment become a problem; the avulsed fragment may also hypertrophy, and some contractures in ACL may develop. A mini-open procedure does not add to the morbidity, overcomes reduction obstacles and allows easy fixation with screws, and can be done even in centers that do not have arthroscopic experience. The key point is accurate reduction and rigid fixation, ensuring no impingement on full extension Conclusions: Mini-open fixation allows accurate, anatomic reduction and stable fixation with screws, and should be the preferred method of fixation for late presenting ACL avulsion fractures; embedding the fragment deep into the crater or size reduction are key to preventing extension deficits.